2017
DOI: 10.1155/2017/9728630
|View full text |Cite
|
Sign up to set email alerts
|

NMR Pore Structure and Dynamic Characteristics of Sandstone Caused by Ambient Freeze-Thaw Action

Abstract: For a deeper understanding of the freeze-thaw weathering effects on the microstructure evolution and deterioration of dynamic mechanical properties of rock, the present paper conducted the nuclear magnetic resonance (NMR) tests and impact loading experiments on sandstone under different freeze-thaw cycles. The results of NMR test show that, with the increase of freezethaw cycles, the pores expand and pores size tends to be uniform. The experimental results show that the stress-strain curves all go through four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The system consists of a specially shaped striker, an incident bar, a transmission bar, an absorption bar, and a damper. The incident bar, transmission bar, and absorption bar are all 40Cr steel with a longitudinal wave velocity of 5400 m/s, a density of 7810 kg/m 3 , and an elastic modulus of 240 GPa [30,38,46]. Two strain gauges are attached to the incident and transmission bars to record the deformation of the two bars.…”
Section: Ucs and Shpb Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The system consists of a specially shaped striker, an incident bar, a transmission bar, an absorption bar, and a damper. The incident bar, transmission bar, and absorption bar are all 40Cr steel with a longitudinal wave velocity of 5400 m/s, a density of 7810 kg/m 3 , and an elastic modulus of 240 GPa [30,38,46]. Two strain gauges are attached to the incident and transmission bars to record the deformation of the two bars.…”
Section: Ucs and Shpb Testsmentioning
confidence: 99%
“…In Figure 10, the transmitted wave (Tr) basically overlaps with the curve of the sum (In + Re) of the incident and reflected waves, indicating that the specimen is basically in the state of stress equilibrium before reaching the peak strength during dynamic loading and the test result is reliable. In addition, the inertial effects are ignored because there is no global force difference in the sandstone specimen to induce inertial forces [38,46].…”
Section: Mechanical Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…From the microscopic perspective, Zhou et al [21] investigated the effect of F-T cycles on the microscopic damage and dynamic mechanical properties of sandstone. e studies by Ke et al [22] show that the pore structure obviously changed with increasing F-T cycles and then an evolution equation for predicting the dynamic peak strength of sandstone after F-T cycles was put forwarded. Based on the above summary, it is clear that the number of F-T cycles was taken as a variable to study rock mechanical and fracture behavior in cold region engineering [23].…”
Section: Introductionmentioning
confidence: 99%
“…But the damage, which is defined by total power and dissipated energy, increases with the increase of cycle times. Ke et al [37,38] conducted NMR tests on rocks after freezethaw cycle (freeze-thaw temperature ranges from − 20°C to 20°C, with cycles of 0, 20, 60, 100, and 140 times, respectively) and did dynamic experiments on rocks under strain rate (75 s − 1 ) using the SHPB system. It is found that, with the increase of freeze-thaw cycle, the porosity of sandstone increases, the evolution of pore size tends to be uniform, the dynamic peak stress decreases, and the energy absorption increases.…”
Section: Introductionmentioning
confidence: 99%